Case Report: Blepharophimosis and Ptosis as Leading Dysmorphic Features of Rare Congenital Malformation Syndrome With Developmental Delay – New Cases With TRAF7 Variants - Paprocka, Justyna; Nowak, Magdalena; Nieć, Maria; Janik, Izabela; Rydzanicz, Małgorzata; Robert, Śmigiel; Klaniewska, Magdalena; Rutkowska, Karolina; Płoski, Rafał; Jezela-Stanek, Aleksandra (Frontiers in Medicine, 2021)
Germline variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) gene have recently been described in about 50 patients with developmental delay and cardiac, facial, and digital anomalies (CAFDADD). We aimed to depict further the clinical and genetic spectrum associated with TRAF7 germline variants in two additional patients, broaden the mutational spectrum, and support the characteristic clinical variety to facilitate the diagnostics of the syndrome among physician involved in the evaluation of patients with developmental delay/congenital malformations.